Incidence of subarachnoid haemorrhage in the Aconcagua Valley, Chile: a community-based, prospective surveillance project. Issue 7 (25th June 2010) - Alvarez, Gonzalo; Cox, Pablo; Pairoa, Mauricio; García, Maritza; Delgado, Iris; Lavados, Pablo M
Abstract : Background: An epidemiological surveillance project was set up in Central Chile to detect cases of subarachnoid haemorrhage (SAH) and its incidence. Methods: Community-based prospective surveillance project carried out between 1 July 2000 and 30 June 2003, in the Aconcagua Valley in Central Chile. The authors ascertained all possible cases using multiple overlapping sources. Incidence rates were age–sex-adjusted. Results: The authors identified 33 first-ever cases; 19 were women. The mean age (SD, range) was 50.7 (17.9, 16 to 82). The incidence per 100 000 age–sex adjusted to the world population was 5.1 (4.4 men, 5.6 women). The 30-day case-death rate was 54.5% (95% CI 38.0 to 70.2), and the prehospital death rate 21.2% (95% CI 10.7 to 37.7). Conclusions: The incidence rate in Aconcagua is notably similar to that reported previously in Northern Chile and lower than in many high-income western populations. The lower incidence rates found in these two Chilean populations might be due to their younger age. A trend towards a higher 30-day case-death rate found in Central Chile is possibly associated with its higher rurality and therefore lesser accessibility to preventive measures and medical care.